Astragalus polysaccharides decrease proliferation, migration, and invasion but increase apoptosis of human osteosarcoma cells by up-regulation of microRNA-133a - Chu,Yanchen (2018)
Osteosarcoma (OS) has a high incidence, malignity, and frequency of recurrence and metastasis. In this study, we aimed to explore the potential anti-cancer effects of Astragalus polysaccharides (APS) on human OS MG63 cells as well as underlying mechanisms. Viability of MG63 cells was assessed by CCK-8 assay to determine the adequate concentration of APS. Then, effects of APS on MG63 cell proliferation, cell cycle distribution, apoptosis, and migration and invasion were analyzed by BrdU incorporation, PI staining, flow cytometry, and transwell assays, respectively. The expression levels of proteins involved in these physiological processes were assessed by western blot analysis. Afterwards, miR-133a level in APS-treated cells was determined by qRT-PCR, and whether APS affected MG63 cells through regulation of miR-133a was determined. Finally, the activation of c-Jun N-terminal protein kinase (JNK) pathway was detected. We found that APS treatment suppressed the viability, proliferation, migration, and invasion of MG63 cells, as well as induced cell apoptosis. Moreover, APS enhanced the expression of miR-133a in MG63 cells. Knockdown of miR-133a reversed the APS treatment-induced MG63 cell proliferation, migration and invasion inhibition, as well as cell apoptosis. Furthermore, APS inactivated JNK pathway in MG63 cells. Knockdown of miR-133a reversed the APS treatment-induced inactivation of JNK pathway in MG63 cells. To conclude, APS repressed proliferation, migration, and invasion while induced apoptosis of OS MG63 cells by up-regulating miR-133a and then inactivating JNK pathway.